Smartphone Addiction of Early Adolescents During COVID-19 Pandemic - Langgersari Elsari Novianti; Made Jelita Dwi Lestari (Daengku: Journal of Humanities and Social Sciences Innovation, 2022)
These days, smartphone seems to be inseparable from everyone’s lives, with increasing usage by adolescents in Indonesia. Besides its numerous benefits in one’s life, smartphone usage might lead to smartphone addiction. This cross-sectional study was conducted to obtain empirical evidence of smartphone addiction and smartphone usage behavior in early adolescents, aged 12-15 years old during Covid-19 pandemic. This study was conducted in November 2020, through an online platform (Google Form). Smartphone addiction was assessed by Smartphone Addiction Scale – Short Version (SAS-SV) in Bahasa Indonesia. Smartphone usage behavior was assessed using an alternate-choice format question about activities with their smartphone and the duration. There were 120 participants obtained using convenient sampling. These participants were mostly aged 14 (55%), from West Java (85.8%), female (60%), and owned a smartphone (95%). Based on the cut-offs, 56.7% of the participants had smartphone addiction (male 22.5%, female 34.2%). This finding implies that an intervention program is needed to reduce or prevent smartphone addiction for early adolescents in Indonesia. Dominant dimensions of smartphone addiction were positive anticipation, daily-life disturbance, and overuse. Duration of smartphone usage per day was mostly 3,5-6 hours per day, those who were addicted tend to spend more time with their smartphone. There was also no significant difference in gender (t(118)=-0,78; p=0,44). The limitation of this research is the limited generalizability of results due to the sampling method used. For future research, we suggest using probability sampling techniques and use duration report from smartphone application to measure it more objectively.